(untitled) (Educação e Pesquisa, 2021)
In this paper, the child participation in collective actions in dialog with the academic production about the Movimento Nacional de Meninos e Meninas de Rua (MNMMR) - National Movement of Street Boys and Girls - and the Sem Terrinha - Little Landless -, a collective of children linked to the Movimento dos Trabalhadores Rurais Sem Terra (MST) - Landless Workers’ Movement is analyzed. The text seeks to reveal the participation of children in each movement, in the tension between the legal provisions on the rights of the child and their concrete experiences. When seeking to understand the meaning of fulfilling children’s rights in their daily lives, the perspective of rights governance, the relationship with the State and the political dimension stand out in each movement. The intent was to discuss the conceptions of participation and “protagonismo” faced by the hierarchical relations of power between adults and children, both in the organization and management of movements and in the legitimation of discourses. Thus, the work contributes to the theories of the studies of social movements and collective actions, since it demonstrates that the concepts of agency and participation cannot be taken as a priori assumptions, as they demand analysis of the conditions and contradictions for their effectiveness. In this direction, the understanding of the child as a social actor is revealed, in both movements, as a way of overcoming the victim mentality in order to occupy the place of a subject who collectively fights for his/her rights.